2005
DOI: 10.2298/zmspn0508009s
|View full text |Cite
|
Sign up to set email alerts
|

Fungi and ochratoxin A: Frequency in food and raw materials for their production in Serbia

Abstract: Contamination of various types of foods (cereals and their products, raisins dry sausages, cheese) with moulds and ochratoxin A (OTA) was examined. All samples were contaminated with moulds to a different degree. About 25% of wheat samples from the localities Niš and Leskovac, 70% from the locality Kikinda, graham flour (1 sample), barley flakes (1 sample), graham bread barley bread, 60% of "healthy food" product samples, 20% of dry sausage samples and 20% of melted cheese samples were contaminated with OTA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Cerelac and milk powder replaced the second position in contamination with A. niger and Penicillium , respectively (Table ). These results previously obtained by Skrinjar et al reported that the most frequent fungi contaminating cornflakes were A. flavus , Eurotium herbarioum and Penicllium aurantiogriseum . Ismail et al found that A. flavus was highly isolated from cerelac and from baby foods on P‐PCNB medium.…”
Section: Resultssupporting
confidence: 76%
“…Cerelac and milk powder replaced the second position in contamination with A. niger and Penicillium , respectively (Table ). These results previously obtained by Skrinjar et al reported that the most frequent fungi contaminating cornflakes were A. flavus , Eurotium herbarioum and Penicllium aurantiogriseum . Ismail et al found that A. flavus was highly isolated from cerelac and from baby foods on P‐PCNB medium.…”
Section: Resultssupporting
confidence: 76%
“…OTA in wines according to various authors(33)(34)(35)(36)(37)(38)(39) OTA was detected in vinegars, too. Majerus et al(30) pointed out the presence of this toxin in 50% of the wine vinegar samples analysed.…”
mentioning
confidence: 85%
“…Some researchers (33,34) found that the production of OTA may take place in the vineyard, where several factors affect fungal development and OTA accumulation. These factors include: a) climatic conditions and latitude, b) contact between barriers and relevant mycotoxigenic fungi, c) wounds or injuries that allow the fungus penetration into the fruit and predispose it to infec-UDC: 615.9:632.25:634/.635 DOI: 10.2298/APT1344103S BIBLID: 1450-7188 (2013) 44, 103-113 Review 109 tion, d) grape cultivation practices, including the use of fungicidal treatments and phytosanitation, and e) the wine-making techniques, including the type of maceration and conditions of fermentation (34,35,36,37,38,39). Some data on the presence of OTA in wines are given in Table 9.…”
Section: Occurrence Of Ota In Winesmentioning
confidence: 99%
“…Ochratoxin A was detected in 20.2% of the samples of melted cheese collected from Serbian markets and 60% of the samples of healthy food: corn, wheat, oats, rice and dry grapes (Table 3) [56]. The concentration of ochratoxin in food products defined by the legislation is 10 μg/kg [2].…”
Section: Mycotoxin Contaminationmentioning
confidence: 99%